Development of Special Needs Education in Lumbini Province - Yadav , Keshav Ram (Journal of Deukhuri Multiple Campus, 2026)
This research study is related to the development of the special education in Lumbini province in Nepal and Dang district is taken as the sample of the study. This research article is a case study which is qualitative research design and interpretivism paradigm. In this research data were collected from the disabled students through focus group discussion and interview with head teacher, resource teachers of Secondary Schools of Dang district. The students said that there are good facilities for lodging and fooding in hostel. Resource teacher and other senior students also help in teaching and playing games. The other friends in inclusive class are also help to the disabled students in reading and writing. They also get writer in exam. There is main problem is inefficient number of resource teacher and trained teacher for teaching computer, teaching musical instruments and teacher for helping the students in playing games. From 2074 B.S. there is limitation of resource teacher due to this limitation of resource teacher students are facing problems in teaching learning process. The researcher feel that the government must be prepared a new plan for the disabled students to provide technical skills due to this technical skill the life style of the disabled students become easier.